PENGARUH PENERAPAN WRAP AROUND SYSTEM TERHADAP PENGURANGAN BERAT KARTON BOX - I Putu Wiradi Pradipta; I Nyoman Astawa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
Packaging plays an important role as it serves as a container that protects products from damage, from the factory to the hands of consumers. Besides functioning as protection, packaging also acts as a communication medium between the product and the consumer by providing information about the product's features, types, and characteristics. In the industry, paper and cardboard packaging are commonly used due to their ability to protect products and their environmentally friendly properties, being biodegradable and recyclable. This research aims to analyze the impact of applying the wrap-around system in reducing the weight of cardboard boxes. The study shows that manual packaging of PET products using conventional cardboard requires a standard cardboard weight of 373.32 grams to maintain the strength of the folds. To reduce product defects, the implementation of the wrap-around system is considered more efficient than conventional methods. In this method, the design of the cardboard box is changed from conventional folds to wrap-around folds, allowing the weight of the cardboard to be reduced without compromising the quality of the folds. The average weight of cardboard in the wrap-around system is 356.95 grams, contributing to the reduction of Non-B3 waste by reducing the weight of the cardboard boxes.